Optimal Design Automation Tool for LLC Converter Based on Time Domain Modelling - Wei, Yuqi; Mantooth, Alan (2021 IEEE Design Methodologies Conference (DMC), 2021)
LLC converter is a popular topology due to its wide range soft switching operation capability. However, optimal design for LLC converter is always challenging due to the complexity of circuit. To simplify the analysis and design, only the fundamental harmonic of the circuit voltages and currents are considered, which will lead to considerable errors. In this article, an optimal design methodology is proposed for LLC resonant converter based on accurate time domain analysis. Two operating points, minimum input voltage with maximum output power and maximum input voltage with minimum output power, are considered. Comprehensive design considerations are included in the proposed design algorithm. The transformer primary resonant inductor root-mean-square (RMS) current and transformer secondary rectifier RMS current are selected as the optimization objective to achieve automated design of LLC converter. Experimental results are presented to validate the effectiveness of the proposed automated design tool.